2003
DOI: 10.3748/wjg.v9.i6.1196
|View full text |Cite
|
Sign up to set email alerts
|

A gene encoding an apurinic/apyrimidinic endonuclease-like protein is up-regulated in human gastric cancer

Abstract: A gene named GCRG213 was identified in human gastric adenocarcinoma. It encoded an APE-like protein which was probably a new member of the APE family. GCRG213 was over-expressed not only in gastric cancer, but also in its precancerous leisions. The role of GCRG213 expression in carcinogenesis needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…We have identified a critical protective role of APE-1 acetylation in Bax-mediated GEC apoptosis by H. pylori . As there are some reports that APE-1 levels are altered in gastric neoplasia,41, 42 our finding that H. pylori infection enhances APE-1 acetylation in gastric epithelial cells suggests that the acetylation status of APE-1 may influence development of gastric cancer. Future studies are required to assess how mutation of APE-1 at its N-terminal Lys residues causes mitochondrial translocation of Bax and induction of host cell apoptosis to prevent potential loss of their niche thereby increasing the opportunity to permit chronic or persistent infection.…”
Section: Discussionsupporting
confidence: 51%
“…We have identified a critical protective role of APE-1 acetylation in Bax-mediated GEC apoptosis by H. pylori . As there are some reports that APE-1 levels are altered in gastric neoplasia,41, 42 our finding that H. pylori infection enhances APE-1 acetylation in gastric epithelial cells suggests that the acetylation status of APE-1 may influence development of gastric cancer. Future studies are required to assess how mutation of APE-1 at its N-terminal Lys residues causes mitochondrial translocation of Bax and induction of host cell apoptosis to prevent potential loss of their niche thereby increasing the opportunity to permit chronic or persistent infection.…”
Section: Discussionsupporting
confidence: 51%
“…Previously, we reported that treatment with hydrogen peroxide as well as infection with H. pylori, but not Campylobacter jejuni, enhanced APE-1/Ref-1 expression in human gastric epithelial cells (32). Moreover, altered levels or cellular location of APE-1/Ref-1 have been found in some cancers, including ovarian and prostate (33,34), while an APE-1/Ref-1-like gene was recently shown to be up-regulated in gastric cancer (35).…”
Section: Interleukin-8 Induction By Helicobacter Pylori In Gastric Epmentioning
confidence: 99%
“…Furthermore, APE-1/Ref-1 itself is regulated by ROS and other environmental stimuli (25,26,28,61), and it has been suggested that the induction of IL-8 and other chemokines by H. pylori is redox sensitive and may depend on ROS-mediated activation of NF-B and AP-1 in gastric epithelial cells (17). Interestingly, an APE-1/Ref-1-like gene has been associated with gastric cancer (35) and H. pylori itself has been implicated in gastric carcinogenesis (2,62). Taken together, we believe that APE-1/Ref-1 plays a unique role in sensing oxidative stress and coordinating molecular events ranging from DNA repair and transcription factor regulation.…”
Section: Ape-1/ref-1 Is Involved In Il-8 Promoter Activationmentioning
confidence: 99%
“…Our previous study [22] identified an upregulated transcript, named gastric cancer related gene 213 (GCRG213), in human gastric adenocarcinoma. BLAST analysis of GCRG213 sequence indicated 88% homology with human LI and revealed a putative conserved domain, apurinic/apyrimidinic endonucleas1 (APE), in GCRG213-ORF.…”
Section: Introductionmentioning
confidence: 99%